Active methodologies for learning in the Higher Education Institution (Research, Society and Development, 2022)
The present study aims to thematize about the active methodologies in the Higher Education Institution. Therefore, it aims to bring a brief contextualization about the history of education, to know the concepts, role of the teacher and the fundamentals of active methodologies, in order to understand the positive and negative impacts on the teaching-learning process of university students. Additionally, point out the active methodologies as strategic measures during the pandemic context, in which classes migrated from the face-to-face modality to the remote environment. Methodologically, it is guided, in the bibliographic research, through the selection of articles to answer the issues mentioned above. Thus, the articles were analyzed, selected and discussed based on thematic categories. The article is delineated in sections, with the second section divided into four subsections, namely: 1) it presents a brief history of education; 2.0) addresses the concept of active methodologies, following: 2.1) the role of the teacher; 2.2) advantages and impacts for university students; 2.3) challenges for implementation and 2.4) influence of the COVID-19 Pandemic. It is concluded that active methodologies provide the faculty with resources to stimulate reflective actions in university students, forming free individuals, endowed with autonomy and capable of dealing with problems, thus becoming able to build their own paths. The research collaborated not only in the amplification of the knowledge of the subject, but also to encourage teachers to consider them and gradually insert them in their educational practices.